ChemInform Abstract: Crystal Structures of Cristobalite‐Type and Coesite‐Type PON Redetermined on the Basis of Single‐Crystal X‐Ray Diffraction Data. Issue 5 (January 2016) - Bykov, Maxim; Bykova, Elena; Dyadkin, Vadim; Baumann, Dominik; Schnick, Wolfgang; Dubrovinsky, Leonid; Dubrovinskaia, Natalia
Abstract: Single crystals of cristobalite‐type PON (cri‐PON) are prepared by a two‐step condensation process starting with the reaction of POCl3 and liq.